A new subgenus and three new species of leafcutter bees, Megachile (Austrosarus) (Hymenoptera, Megachilidae) from central Brazil - Raw, Anthony (Zootaxa, 2006)
A new subgenus, Austrosarus, and three new species of Megachile from central Brazil are described. Austrosarus shares some characteristics with the subgenera Austromegachile, Chrysosarus and Sayapis. M. frankieana occurs in the Federal District of Brasília, in Goias and Minas Gerais states and in eastern and southern Mato Grosso, while M. diasi and M. candanga have been collected only in the Federal District. A key is provided to identify the females.